Should the U.S. Federal Government Expand Its Efforts to Help the Poor? Attitudes of Conservatives, Liberals, Republicans, and Democrats. - Yen, Steven T.; Zampelli, Ernest M. (Journal of Poverty, 2024)
Even when controlling for big versus small government philosophies, this paper reports quantitatively significant cleavages in the probabilities of supporting increased federal antipoverty efforts that persist between conservatives and liberals, and Republicans and Democrats. However, predicted conditional probabilities show that support for increased welfare spending or federal responsibility in raising the standard of living of the poor is not overwhelming, even among liberals and Democrats, although support for increased federal assistance to the poor is fairly strong, even among conservatives and Republicans. Hence, we consider assertions that conservatives and Republicans do not care about the poor to be extreme and unsupported.